Distribution and lateral mobility of voltage-dependent sodium channels in neurons [published erratum appears in J Cell Biol 1989 May;108(5):preceding 2001] (The Rockefeller University Press, 1988)
Voltage-dependent sodium channels are distributed nonuniformly over the surface of nerve cells and are localized to morphologically distinct regions. Fluorescent neurotoxin probes specific for the voltage- dependent sodium channel stain the axon hillock 5-10 times more intensely than the cell body and show punctate fluorescence confined to the axon hillock which can be compared with the more diffuse and uniform labeling in the cell body. Using fluorescence photobleaching recovery (FPR) we measured the lateral mobility of voltage-dependent sodium channels over specific regions of the neuron. Nearly all sodium channels labeled with specific neurotoxins are free to diffuse within the cell body with lateral diffusion coefficients on the order of 10(- 9) cm2/s. In contrast, lateral diffusion of sodium channels in the axon hillock is restricted, apparently in two different ways. Not only do sodium channels in these regions diffuse more slowly (10(-10)-10(-11) cm2/s), but also they are prevented from diffusing between axon hillock and cell body. No regionalization or differential mobilities were observed, however, for either tetramethylrhodamine- phosphatidylethanolamine, a probe of lipid diffusion, or FITC-succinyl concanavalin A, a probe for glycoproteins. During the maturation of the neuron, the plasma membrane differentiates and segregates voltage- dependent sodium channels into local compartments and maintains this localization perhaps either by direct cytoskeletal attachments or by a selective barrier to channel diffusion.